Analisis Doktrin Perang Yang Adil (Just War ) dalam Kasus Serangan Siber Rusia Terhadap Georgia Tahun 2008 - Aryuni Yuliantiningsih (Universitas Muhammadiyah Purwokerto, 2021)
Cyberwarfare is a warfare with information technology that has developed. It has not been regulated in humanitarian law. Cyber attacks have been carried out by several countries by ignoring the Just War Theory. This article aims to analyze the implementation of the Just War theory in cyber warfare according to international humanitarian law in the case of conflict between the Russian and Georgia in 2008. The research method use the normative juridical and using secondary data sources. Qualitative data using deductive conclusion method. Based on the research results, it is known that the just war theory including jus ad bellum, jus in bello and jus post bellum is not applied in cyberwarfare. The Russian’s cyber attack against Georgia violates the distiction principle , the principle of proportionality and the principles of proportionality. The losses incurred as a result of cyberattacks are not compensated by Russia.Keywords: just war, cyber attack, Russia, Humanitarian law.